The bomb shelter - Talton, Jon (Talton, Jon. David Mapstone mystery., 2018)
"Forty years ago, a Phoenix reporter was killed by a car bomb in one of America's most notorious crimes. Three men went to prison but was the assassination ever really solved? Did the kingpin who ordered the hit get away with it? It's a case custom-made for David Mapstone, the historian-turned-sheriffs deputy. But the past never rests easy in Arizona and when Mapstone's boss, Sheriff Mike Peralta, promises to reopen the investigation, new murders commence."--